2017
DOI: 10.1016/j.bjid.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm and dissection in a patient with syphilitic aortitis

Abstract: In the antibiotic era, aortic aneurysm is a rare complication of syphilis, what makes the diagnostic assumption even more difficult. Nonetheless, this condition should be suspected in patients with aortic aneurysm. Reports of aortic dissection complicating syphilitic aortitis have been distinctly rare in the literature, and their cause-effect relationship has not been definitely established. In this case report, we present a 62-year-old woman with aortic aneurysm and dissection associated with an unexpected di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…In addition, there are symptoms of heart failure, and it is usual for a murmur to be auscultated at the right sternal border 16 ; in our patient, a Grade III systolic murmur was audible in all foci, with high predominance in the aortic focus. The second most common complication is syphilitic aneurysm, which is 3 times less frequent than aortic regurgitation and is detected in 5-10% of patients; Grade II aortic regurgitation, moderate grade aortic valve calcification, and aneurysm of the aortic root and ascending aorta were found in our patient, which is consistent with the literature on the most common location of aneurysms (50% in the ascending aorta, 35% in the aortic arch and 15% in the descending aorta) [17][18][19][20] .…”
Section: Discussionsupporting
confidence: 90%
“…In addition, there are symptoms of heart failure, and it is usual for a murmur to be auscultated at the right sternal border 16 ; in our patient, a Grade III systolic murmur was audible in all foci, with high predominance in the aortic focus. The second most common complication is syphilitic aneurysm, which is 3 times less frequent than aortic regurgitation and is detected in 5-10% of patients; Grade II aortic regurgitation, moderate grade aortic valve calcification, and aneurysm of the aortic root and ascending aorta were found in our patient, which is consistent with the literature on the most common location of aneurysms (50% in the ascending aorta, 35% in the aortic arch and 15% in the descending aorta) [17][18][19][20] .…”
Section: Discussionsupporting
confidence: 90%
“…In the past decade, several cases of syphilitic thoracic aortic aneurysm have been reported with variable clinical presentation such as simultaneous involvement of the brain, spinal cord (neurosyphilis), lungs (pulmonary syphilis), and rupture or dissection of thoracic aortic aneurysm (cardiovascular syphilis) [5,7,[16][17][18][19][20]. Our case is a classic presentation of isolated cardiovascular syphilis presented with a large thoracic aortic aneurysm confirmed with TP-PA testing and radiological imaging.…”
Section: Discussionmentioning
confidence: 63%
“…Since ascending and thoracic aorta are rich in lymphatics, spirochetes have tropism for these aortic segments. [10][11][12][13] The tendency of spirochetes to dwell in the small vessels of the vasa vasorum leads to an adventitial chronic inflammation, mainly in the arterioles that perfuse the media layer. 6 The immune system response involves infiltration of plasmacytes and lymphocytes into the aortic wall layers, creating a diffuse and fibrous thickening of the intima.…”
Section: Discussionmentioning
confidence: 99%
“…7 In fact, the vasa vasorum undergoes a process of endarteritis obliterans and necrosis of the media, and the elastic tissue of the vessel is destroyed and replaced by scar tissue. 11,12 This inflammatory process can continue for a long time after the initial infection, which can explain the cardiovascular manifestations of syphilis aortitis generally occurring 10 to 30 years after the original untreated infection. 2,7,14 Indeed, Heggtveit 15 reported that among patients with syphilitic aortitis, 50% of the aortic aneurysms developed in the ascending aorta and 35% in the aortic arch, followed by 15% in the descending aorta.…”
Section: Discussionmentioning
confidence: 99%